Partisipasi Lembaga Pengelola Sampah Dalam Mewujudkan Tujuan SDGS di Kelurahan Padang Terubuk - Azzahra, Apriola; Putra, Ariandra Pratama; Pramana, Chelvin Abdi; Safitri, Desta; Mizan, Khairul; M, Maisarah; Butar Butar, Novi Indah; Fadilah, Rizki; Aisyah, Siti; Fadillah, Syarifah; Anindya, Thalita Adristi; Fitri, Yolanda; Putri, Risky Arya (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Waste management is one of the most urgent environmental problems in Indonesia, including in Pekanbaru City. Padang Terubuk Village faces challenges such as limited public awareness and inadequate waste facilities. To address this, the community established a Waste Management Institution (LPS) as a local actor in managing household waste and promoting the 3R principles (Reduce, Reuse, Recycle). This article explains the role of LPS in achieving the Sustainable Development Goals (SDGs) through the MBKM Community Service Program. The method applied was participatory, including seminars, coordination with stakeholders, household socialization, and digital innovation through Instagram branding. The results show that LPS succeeded in raising awareness, encouraging waste sorting, and building collaboration between residents, students, and the government. This integration proves that community-based institutions are essential in supporting environmental sustainability and urban development.